The Utilization of Google Form as Learning Media in Statistics Course - Yunitasari, Ika; Sudirman, Ade (Journal of English Education Studies, 2021)
This research aims to investigate the utilization of Google form in Statistics course at English education department, teacher training and education faculty, University of Mathla’ul Anwar. The researcher conducted qualitative research with literature study design. The methods used were bibliographical searches and learning descriptions using Google Forms. The source of literature investigated were journal articles, continuous article, books and articles relating with Google Form as learning media. The participants of the research were 6th semester students of English Education Department. So far, Google Forms are more often used for evaluation or assessment of learning, even though it also can be used as learning media to teaching a specific material by attaching videos and graphics to support material explanation. Google forms is cheap and effective learning media because it does not need more quota to access and specific application, it merely has to have a Google account.